Ilmu dalam Tinjauan Filsafat: Ontologi, Epistemologi, dan Aksiologi - Munip, Al (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
Science has specific components, such as objects, statements, propositions, and characteristics. These four aspects are the focus of three philosophical foundations: ontology, epistemology, and axiology. This article is written to discuss science from a philosophical perspective, namely ontology, epistemology, and axiology. In this article, the author uses the literature study method by reviewing various books and other scholarly works relevant to the topic discussed. From the analysis, it can be concluded that ontology focuses on the nature of